Evaluation of the Energy Efficiency of Industrial Furnaces Based on the Modeling of Fuel Consumption Modes - Ya. L. Shenets (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2022)
A number of industrial plants that manufacture modern products use industrial furnaces in their technology. During their operation, it is necessary to comply not only with the current legislation, but also with the norms of consumption of fuel and energy resources. The growth of tariffs for energy resources has led to a significant increase in the energy component of costs price in the structure of the cost of production. As a result, even a small (several percent) change in the cost price can bring any industrial enterprise, including the most modern ones that use gas processing equipment, into the category of unprofitable. Having referred to technical regulatory legal acts, the present article proposes an energy efficiency indicator that allows monitoring energy efficiency at existing industrial plants with industrial furnaces. The world experience of operating glass industry furnaces is considered, existing approaches to determining the energy efficiency of this technology are presented. Based on the analysis of daily indicators of the operating modes of the technological line, methods have been proposed for estimating the rate of reduction in energy efficiency of a flat glass production line and forecasting the total and specific consumption of fuel and energy resources of industrial furnaces (in terms of a continuous glass furnace). The presented methods and the numerical calculations obtained for reducing the energy efficiency of a glass furnace make it possible to predict fuel consumption and form a correct annual application for its required volume to a gas supply organization, as well as evaluate the energy efficiency of production operating an industrial furnace and calculate the energy consumption rate for the output of a unit of production. Ultimately, more accurate determining of the cost of production of a particular industrial enterprise is achieved.